Climate Analogues Training in Dar es Salaam, Tanzania2014 - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
On July 21-25 CCAFS East Africa brought together thirty six (36)policy makers and researchers from National Agricultural Research and Extension Systems (NARES), Universities and Government Ministries in Tanzania to learn about the CCAFS Analogue tool and its application. Photos by P.Kimeli